2023
DOI: 10.1098/rsbl.2022.0457
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous distribution of sex ratio distorters in natural populations of the isopod Armadillidium vulgare

Abstract: In the isopod Armadillidium vulgare , many females produce progenies with female-biased sex ratios, owing to two feminizing sex ratio distorters (SRD): Wolbachia endosymbionts and the f element. We investigated the distribution and population dynamics of these SRD and mitochondrial DNA variation in 16 populations from Europe and Japan. Confirming and extending results from the 1990s, we found that the SRD are present at variable frequencie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 49 publications
1
10
0
Order By: Relevance
“…We found that 29.9% of individuals carried only the f element, 15.2% carried only Wolbachia , 0.6% carried both SRD and 54.3% carried none. While both SRD were mostly found in females, they were also sometimes present in males, as previously reported (Durand et al ., 2023). Wolbachia -infected individuals carried one of the three previously known Wolbachia strains of A. vulgare : w VulC (n=22), w VulM (n=25) or w VulP (n=83).…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…We found that 29.9% of individuals carried only the f element, 15.2% carried only Wolbachia , 0.6% carried both SRD and 54.3% carried none. While both SRD were mostly found in females, they were also sometimes present in males, as previously reported (Durand et al ., 2023). Wolbachia -infected individuals carried one of the three previously known Wolbachia strains of A. vulgare : w VulC (n=22), w VulM (n=25) or w VulP (n=83).…”
Section: Resultssupporting
confidence: 86%
“…Yet, the f element was the dominant SRD in 4 out of 6 populations we studied and was rising in frequency in Niort (Juchault et al ., 1992). Overall, the f element is more widespread than Wolbachia in A. vulgare populations (Juchault et al ., 1993; Durand et al ., 2023). Previously proposed explanations include a higher fitness cost entailed by Wolbachia relative to the f element and occasional paternal transmission of the f element (which some males carry, Figure 1) enabled by masculinizing epistatic alleles (Juchault et al ., 1992; Rigaud and Juchault, 1993; Rigaud, 1997; Rigaud and Moreau, 2004; Cordaux and Gilbert, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…duebeni and G . roeselii or Wolbachia pipientis in the isopod Armadillidium vulgare —are always more frequent in females than in males (which makes sense given that the parasites convert infected males into females) [ 20 , 23 , 89 ]. The high prevalence and above all the homogeneity of Nosema haplogroups across the geographic range of G .…”
Section: Discussionmentioning
confidence: 99%
“…However, the analysis of infection patterns relative to sexes showed that there were no significant differences in prevalence between sexes in most populations. Yet, parasites that have been shown to be sex ratio distorters-such as N. granulosis in G. duebeni and G. roeselii or Wolbachia pipientis in the isopod Armadillidium vulgare-are always more frequent in females than in males (which makes sense given that the parasites convert infected males into females) [20,23,89]. The high prevalence and above all the homogeneity of Nosema haplogroups across the geographic range of G. balcanicus is therefore puzzling.…”
Section: Plos Pathogensmentioning
confidence: 99%